Intrapersonal Communication Driving Childfree Decisions Among Unmarried Indonesian Women - Prayoga, Inggar; Junita Triwardhani, Ike (UIR Press, 2026)
The phenomenon of being childfree by choice is gaining traction in Indonesia, yet it remains a subject of significant social debate within the country's pronatalist culture. This study investigates the intrapersonal communication dynamics driving the proactive decision-making process of unmarried adult women who voluntarily choose not to have children. Adopting a qualitative research design with a phenomenological approach, data were collected through in-depth interviews and participant observations with five key informants and four supporting experts. The analysis is theoretically grounded in the integration of intrapersonal communication processes with the four phases of proactive decision-making: Intelligence, Design, Choice, and Implementation. The findings reveal that the decision to be childfree is fueled by a complex interplay of